When Expectations Meet Reality: Tourist Satisfaction at Tamban Beach, Malang Regency, Indonesia - Nadhifah, Salsabila Iftinan; Dinanti, Dian; Hidayat, Ar Rohman Taufiq; Supriyadi (Perencanaan Wilayah dan Kota FT UB, 2025)
The tourism sector plays an important role in regional development by contributing to economic growth and improving community welfare. Increased tourist arrivals can significantly support the growth of Gross Regional Domestic Product (GRDP) and stimulate the development of Micro, Small, and Medium Enterprises (MSMEs) in destination areas. In this context, repeat visitation is particularly important, as returning visitors often account for a substantial proportion of total visitors. Tourist satisfaction, which is closely related to tourists’ evaluations of destination performance during their visit, is widely recognized as a key factor influencing revisit intention, particularly in relation to the four fundamental tourism components known as the 4As (attraction, accessibility, amenities, and ancillary services). Tamban Beach in Malang Regency has considerable natural potential. However, it continues to face several challenges that may affect visitor satisfaction and their intention ro revisit. This study aims to examine the determinants of revisit intention through tourist satisfaction by analyzing visitors’ experiences with the 4A components at Tamban Beach. The study involved 120 respondents and employed the Kano Model and behavior mapping as data analysis techniques. The results classify the attributes of the 4A components based on Kano categories and map their spatial distribution, providing insights to support improvements in tourism services quality at Tamban Beach.